A network topology-based voltage stability index for radial distribution networks - Eminoğlu, Ulaş; Hakan Hocaoglu, M. Hakan (My University, 2009)
This paper presents a network topology-based voltage stability index for identifying the most sensitive bus to the voltage collapse in the radial distribution networks. The developed index is based on the transferred active and reactive power equation of the distribution line. Network topology algorithm based on the bus-injection to branch-current (BIBC) matrix has been used for implementation of developed stability index to the radial distribution networks. The performance of the index is tested on different loading conditions for different load models and different substation voltage levels. Results suggest that the proposed index is reliable and can easily be applied to the modern radial distribution networks which have distributed generation (DG) sources and/or voltage controllers. © 2010 Elsevier B.V., All rights reserved.
Keywords: Critical bus; Distributed generation; Radial distribution network; Static load modal; Voltage stabillity indes